Spatial Analysis of Slope, Wind Direction, and Wind Speed in the Environmental Science Master’s Field Laboratory in Forest Areas with the Special Purpose of Wanadipa, Diponegoro University - Anggara Apriyan Pradana; Maryono Maryono; Fuad Muhammad (Journal of Bioresources and Environmental Sciences, 2025)
Higher Education institutions play an important role in the development of Science and Technology. They are supported by adequate facilities for carrying out educational activities, research, and innovation development through Special Purpose Forest Areas (KHDTK/Kawasan Hutan Dengan Tujuan Khusus). KHDTK is a forest area designated by the government for public purposes such as research and development, education and training, and religion and culture, the management of which is given to customary law communities, educational institutions, research institutions, and social and religious institutions. The research aims to identify wind direction, wind speed, and slope. This research uses a quantitative approach with the instruments of ArcGIS and Google Earth Pro and the analysis technique of WRPlot.The research results show that the wind speed and direction in 2023, between January and March, in the Undip MIL Field Laboratory area was strong, most of which blew from the northwest. In April, the wind speed decreased, and the direction of wind gusts changed starting from the south. Stable conditions were shown between May and December, with an average wind speed of 2.7 m/s and some wind gusts coming from the southeast. Moreover, the MIL UNDIP Field Laboratory has three types of slope classes: flat, gentle, and wavy slopes, with a value of 6.6%, 13.3%, and 20%, respectively.